Remarks on sports tourism as a reflection on "Relations between tourism and sport concerning the organization of tourism studies" by J. Kotus - Liszewski, Stanisław (Turyzm/Tourism, 2016)
The text is a dispute with the author of the article, who attempted to define the concept of “sports tourism”. The article is published in this issue, on pages 19-25.